Urban Economic Resilience in the Andean Community: a Study of Impulse-Response - Lara, Diego (2024)
T This research examines the imbalance between resilience and urban economies in the countries that make up the Andean Community (CAN). Methodologically, reliable statistical information on economic and urban indicators was collected from the databases of national and international agencies of the four CAN countries. Tests of stationarity, cointegration, exogeneity, and stability conditions were carried out, followed by an investigation of volatility and the principles of transfer to the selected urbanization indicators, using advanced econometric techniques such as orthogonal impulse-response analysis and Cholesky variance decomposition. The findings reveal a gap in urban indicators and urban economic resilience within the CAN, with prosperous countries such as Colombia and Peru showing better results compared to Ecuador and Bolivia. The latter nations demonstrated better adaptability to external shocks. It was also identified that part of the variance of the forecast error of the urban economic growth rate is explained by exogenous shocks to urbanization variables. In conclusion, this study contributes to the understanding of urban economic resilience in the aforementioned countries, enhancing comprehension of the subject and emphasizing the need to examine in depth how nations deal with the negative impacts of urbanization.